IMPROVING PRE-SERVICE MATHEMATICS TEACHERS’ SUBJECR MATTER KNOWLEDGE THROUGH SCHOOL-UNIVERSITY PARTNERSHIP MEDIATED BY LESSON STUDY PROGRAM - Fitriati, Fitriati; Rosli, Roslinda; Hidayat, Arif (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of this study is to explore the power of a school university partnership mediated by lesson study (SUPER-LS) in improving pre-service mathematics teachers’ subject matter knowledge (SMK). This study implemented the SUPER-LS program with 10 pre-services teachers (PSTs), 10 in-service teachers (ISTs) and knowledgeable others to accomplish this objective. The study was executed in two phases: one at the school and the other at the university. Throughout the program, they designed a mathematics curriculum based on the concepts of Realistic Mathematics Education (RME), facilitated an open class, and engaged in post-lesson discussions throughout two cycles of lesson study. Data were collected through observations of lesson study activities and objects, and analyzed using transcript-based lesson study following MKT framework. The study revealed that the SUPER-LS program can enhance collaboration among PSTs to augment their Subject Matter Knowledge (SMK), with specialized content knowledge (SCK) being predominant. Nonetheless, a follow-up program to guarantee that PSTs have rigorous training is essential.